2009
DOI: 10.1111/j.1365-2842.2009.01963.x
|View full text |Cite
|
Sign up to set email alerts
|

Craniofacial morphology in patients with hypophosphataemic vitamin‐D‐resistant rickets: a cephalometric study

Abstract: Hypophosphataemic vitamin-D-resistant rickets (HVDRR) is a hereditary disease mainly transmitted as an X-linked dominant trait and characterized by certain general clinical signs (Filho HM, de Castro LC, Damiani D. Arq Bras Endocrinol Metab. 2006;50:802). In literature, only one study had been published in 1965 on the cephalometric findings in patients with HVDRR (Marks SC, Lindahl RL, Bawden JW. J Dent Child. 1965;32:259). This is the first detailed study on craniofacial characteristics of patients with HVDRR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
12
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 18 publications
3
12
0
Order By: Relevance
“…The present study is based on a higher number of patients with HR in comparison with other studies [Marks et al, 1965; Tracy and Campbell, 1968; Al‐Jundi et al, 2009]. Furthermore, the genetic as well as the biochemical profile of the diseased individuals fulfilled well‐defined diagnostic criteria of HR [Beck‐Nielsen et al, 2010].…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…The present study is based on a higher number of patients with HR in comparison with other studies [Marks et al, 1965; Tracy and Campbell, 1968; Al‐Jundi et al, 2009]. Furthermore, the genetic as well as the biochemical profile of the diseased individuals fulfilled well‐defined diagnostic criteria of HR [Beck‐Nielsen et al, 2010].…”
Section: Discussionmentioning
confidence: 71%
“…Recently, a cephalometric study of 22 Jordanian patients with HR described a shortened anterior cranial base and maxilla as well as reduced mandibular dimensions compared to a healthy age‐ and gender‐matched control group. The cranial base was flattened and HR patients had a skeletal Class III malocclusion [Al‐Jundi et al, 2009]. In addition, anthropometric studies have described an increased cranial length and occipital width as well as increased head circumference in HR patients [Pronicka et al, 2004; Beck‐Nielsen et al, 2010].…”
Section: Introductionmentioning
confidence: 99%
“…In studies on rare diseases, it is an ever‐standing challenge to achieve a reasonable sample size. The previously published cephalometric XLH studies included up to 22 XLH patients . This study, which includes 36 patients, adds further to the total number of reported XLH cases dealing with an assessment of cranial deviations.…”
Section: Discussionmentioning
confidence: 99%
“…XLH affects the cranium in humans , and in HYP mice (the murine model of XLH) . Furthermore, XLH patients have dental abnormalities and endodontically affected teeth are common in adults with XLH .…”
Section: Introductionmentioning
confidence: 99%
“…[39] Cephalometric analysis has demonstrated altered craniofacial morphology in a few studies on rickets patients. [40] Therefore, a possibility of osteomalacic changes exists in the adult population with vitamin D deficiency.…”
Section: Discussionmentioning
confidence: 99%